2021
DOI: 10.1101/2021.08.12.456140
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor learning without movement

Abstract: Current theories of motor control emphasize forward models as a critical component of the brain's motor execution and learning networks. These internal models are thought to predict the consequences of movement before sensory feedback from these movements can reach the brain, allowing for smooth, continuous online motor performance and for the computation of prediction errors that drive implicit motor learning. Taking this framework to its logical extreme, we tested the hypothesis that movements are not necess… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
(214 reference statements)
1
1
0
Order By: Relevance
“…In conclusion, the results from this study show that sensorimotor adaptation to target errors is possible in an online Pong game. It supports the findings of previous studies demonstrating that online experimentation can be as informative if not more than traditional laboratory experiments (Kim et al, 2021; Tsay et al, 2021). The Pong task is less restrictive than the ones that have been used in past lab-based studies.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the results from this study show that sensorimotor adaptation to target errors is possible in an online Pong game. It supports the findings of previous studies demonstrating that online experimentation can be as informative if not more than traditional laboratory experiments (Kim et al, 2021; Tsay et al, 2021). The Pong task is less restrictive than the ones that have been used in past lab-based studies.…”
Section: Discussionsupporting
confidence: 90%
“…Sheahan and colleagues (33) show that planning without executing different follow-through movements is sufficient for learning opposing perturbations simultaneously. Furthermore, Kim and colleagues (34) have recently shown that motor learning in the context of motor adaptation occurs also if the previous movement is withheld. These observations are in line with studies showing that motor imagery improves performance in sports (35,36).…”
Section: Discussionmentioning
confidence: 99%